2015
DOI: 10.1016/j.biomaterials.2015.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Ductile electroactive biodegradable hyperbranched polylactide copolymers enhancing myoblast differentiation

Abstract: Myotube formation is crucial to restoring muscular functions, and biomaterials that enhance the myoblast differentiation into myotubes are highly desirable for muscular repair. Here, we report the synthesis of electroactive, ductile, and degradable copolymers and their application in enhancing the differentiation of myoblasts to myotubes. A hyperbranched ductile polylactide (HPLA) was synthesized and then copolymerized with aniline tetramer (AT) to produce a series of electroactive, ductile and degradable copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 42 publications
(41 reference statements)
0
72
0
Order By: Relevance
“…Meanwhile, heart as a vital organ has special electrophysiological behavior and the cardiac cells were in an electroactive condition. [17][18] It has been demonstrated that conductive polymers may promote the proliferation and differentiation of the electrical stimuli responsive cells, such as the stem cells, [19][20] myoblast cells, [21][22][23] nerve cells [24][25] and the cardiac cells. [26][27][28][29] Therefore, injectable hydrogels with conductivity as cardiac cell delivery vehicle are highly anticipated for cardiac repair.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, heart as a vital organ has special electrophysiological behavior and the cardiac cells were in an electroactive condition. [17][18] It has been demonstrated that conductive polymers may promote the proliferation and differentiation of the electrical stimuli responsive cells, such as the stem cells, [19][20] myoblast cells, [21][22][23] nerve cells [24][25] and the cardiac cells. [26][27][28][29] Therefore, injectable hydrogels with conductivity as cardiac cell delivery vehicle are highly anticipated for cardiac repair.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectra (FTIR) were gathered by samples mixed with potassium bromide (KBr) particles using a spectrometer (Nicolet 6700, Wisconsin, USA) at a resolution of 4 cm −1 and the scans of 128 in the region 4000–500 cm −1 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was found that conductive polymers could tune the properties of cells in electrically sensitive tissues under electrical stimulation, including neural, muscle, cardiac, and bone [8284]. Regenerative biomaterials for the treatment of bone diseases that need surgical intervention have attracted more attention, particularly with extended life expectancies.…”
Section: Synthesis and Properties Of Hybrid Polymersmentioning
confidence: 99%